A multi‐scale hydroclimatic analysis of runoff generation in the Athabasca River, western Canada. Issue 13 (27th February 2013) - Peters, Daniel L.; Atkinson, David; Monk, Wendy A.; Tenenbaum, David E.; Baird, Donald J.
Abstract: A multi‐scale hydroclimatic study of runoff generation in the Athabasca River watershed located in western Canada is presented. Mann–Kendall trend detection tests performed on hydrometric data for the lower Athabasca River (LAR) revealed predominantly significant ( p < 0.05) declines in annual and open‐water season median/mean runoff indices over 1958–2009, with the ice‐influenced season experiencing significant declines in the median and not the mean. The presence or absence of significant declines in the 25 th and 75 th runoff percentiles helped explain these results. The only noteworthy result from the mid‐point of the watershed was a probable ( p < 0.10) decline in median open‐water runoff, which was not seen over the 1913–2009 period. Divergent seasonal runoff trends from the headwater zone were seen since 1958 and back to 1913, increasing ice‐influenced and declining open‐water season runoff trends. Although precipitation was observed to decline over 1958–2009, only the LAR watershed scale annual index emerged as a probable decline. Multiple non‐linear regression analysis indicated that variation in precipitation explained >67% of the annual median/mean LAR runoff variability since 1958. A first‐order precipitation driven hindcasting model suggested that LAR watershed scale runoff may have increased since 1913, warranting further study. A correlation analysis of climatic teleconnections with median/mean runoff indices revealed that the winter North Pacific American index showed a strong, positive association with open‐water runoff. The results from our study demonstrated that potentially inconsistent and/or divergent trend results can be obtained when using different time periods and/or regions of the watershed, emphasizing that extreme caution should be exercised when extrapolating sub‐watershed results to the watershed scale, or to adjacent watersheds. Our multi‐scale study approach also identified the drainage area between Athabasca and Fort McMurray as a zone that influenced runoff declines observed at the LAR watershed scale since 1958, which warrants further investigation with competent hydrological models. Copyright © 2013 John Wiley & Sons Ltd and Her Majesty the Queen in Right of Canada Reproduced with the permission of the Ministry of the Environment.